Impact of Antioxidant Addition to Quail Feed on Progeny’s Antioxidant Status and Glutathione Peroxidase 1 Gene Expression - Karageçili, MR; Karadaş, F (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, the effect of antioxidant supplementation in breeder quail feed on performance of progeny and total antioxidant capacity, glutathione peroxidase concentration and expression level of glutathione peroxidase 1 gene in liver tissue of progeny at hatching and 21-d-old were investigated. A total of 432 Japanese quail (Coturnix japonica) breeders (a total of 432 breeders, 324 female and 108 male) were divided into six groups. Breeder quails in the control group were fed with basal breeder quail diet. Animals in the experimental groups were fed with commercial breeder feed by adding 0.35 mg/kg Sel-Plex, 40 mg/kg L-carnitine, 50 mg/kg DL-methionine, 250 mg/kg vitamin E and 10 mg/kg taurine, respectively. Following the breeder feeding period, a total of 1200 eggs, 200 fertile quail eggs in each group, were placed in the incubator. Hatched chicks were placed in the same trial groups. Progeny was fed with basal chick diet. Breeder quails and progeny were fed ad libitum for four weeks, with constant access to feed and water. The lowest hatchability of total eggs, fertility and hatchability of fertile eggs were determined in the taurine group (77.5%, 91.5%, 84.70%, respectively) (p<0.05). Mid-term embryo mortality did not occur in the Se group (p<0.05). Body weight, feed consumption, body weight gain and feed conversion ratio of progeny did not affect addition of antioxidant (p>0.05). Supplementation of methionine and vitamin E increased glutathione peroxidase enzyme concentration in liver tissue of chicks at hatching (1.575 ng/mg and 1.875 ng/mg, respectively) and 21-d-old (2.739 ng/mg and 2.716 ng/mg, respectively). The addition of antioxidants to the diet increased the total antioxidant capacity in liver tissue at hatching (p<0.05). As a result, antioxidant supplementation to breeder basal diet affected the hatchability of total eggs, fertility, embryonic deaths, and glutathione peroxidase enzyme concentration, total antioxidant capacity and glutathione peroxidase 1 gene expression levels.